Within the asylum‐advocacy nexus: An analysis of Mexican transgender asylum seekers in the United States. Issue 1 (27th June 2019) - Barnes, Nielan
Abstract: Despite that Mexico has experienced significant legislative gains for LGBT rights, why is transphobic violence on the rise, driving increasing numbers to immigrate to the United States, even though the United States also experiences high levels of transphobic violence? This paper uses action‐based research from within the "asylum‐advocacy nexus" to analyze the experiences of Mexican transgender and gender non‐conforming persons within both the Mexican society and the US society and asylum process. Data show early childhood socialization is deeply informed by conservative religious (trans‐ and homophobic) ideas and practices that extend from the family and church into each sector of society—educational, employment, health care, public security, popular culture, sports, etc. Despite some legislative advances and possibilities for empowerment, there remains a programmatic need to address a culture of violence against sexual minorities within family, educational, legal, and public security sectors in both countries.